The Association between Environmental Sanitation and Soil Transmitted Helminths (STH) Coinfection of Tuberculosis Patients in Panti District, Jember Regency - Nita Alfianti; Yunita Armiyanti; Bagus Hermansyah; Enny Suswati; Dini Agustina; Diana Chusna Mufida (Journal of Ners and Midwifery, 2020)
Tuberculosis (TB) is a contagious infectious disease caused by the bacteria Mycobacterium tuberculosis. More than 80% of TB cases attack the pulmonary organs and the rest are extra-pulmonary TB. Indonesia is one of the countries with the high number of tuberculosis cases besides India, China, the Philippines, and Pakistan. Aside from being a country with a high TB incidence, Indonesia is also an endemic country for helminth infections, especially Soil-Transmitted Helminths (STH). The high prevalence of STH infections in Indonesia allows STH coinfection in TB patients to cause decreasing immunity, thus affecting the outcome of TB infection. STH infection is very closely related to environmental sanitation. The purpose of this study was to identify and determine the association of environmental sanitation risk factors to the coinfection of Soil-Transmitted Helminths (STH) in tuberculosis patients in Panti District, Jember Regency. This type of research was observational research with cross-sectional analytic design. Of the 49 TB patients who were undergoing treatment at the Panti Health Center, 32 people were willing to be respondents, but only 25 people collected stool samples. Fisher's test results showed that the incidence of intestinal co-infection in TB patients in Panti District, Jember Regency was 12% and was caused by two STH species, namely A. lumbricoides and Hookworm. Environmental sanitation in TB patients was mostly good, e.g 54.5% of respondents had good environmental sanitation, but there was no significant association between environmental sanitation and the incidence of intestinal co-infection in TB patients in Panti District, Jember Regency (p> 0.05).